A super-tough, high-strength, flame-retardant, self-repairing elastomer composite material and preparation method thereof
By introducing high-density dynamic hydrogen bonds and coordination bonds into the aqueous polyurethane matrix, and the coordination and hydrogen bond cross-linking are performed by gradually dissolving ice, the problem of mutual constraints between the self-healing and mechanical properties of existing elastomer composite materials is solved, and composite materials with high strength, high toughness, high self-healing efficiency and wide temperature domain damping performance are achieved.
Patent Information
- Application Number
- CN202410132787.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-30
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-01-30
AI Technical Summary
The existing elastomer composite materials have mutually restricted between self-healing properties and mechanical properties, and the glass transition temperature is low and the damping temperature range is small, making it difficult to meet the needs of high strength, high toughness, high self-healing efficiency and wide temperature domain damping performance at the same time.
By introducing high-density dynamic hydrogen bonds and coordination bonds into the aqueous polyurethane matrix, the coordination and hydrogen bond cross-linking are performed by gradually dissolving ice in the reaction solution to form a composite material with high mechanical properties, self-healing properties, damping properties and flame retardant properties.
The ultra-tough, high-strength flame retardant self-healing elastomer composite material produced has high toughness, high strength, high elongation of break, high modulus, wide damping temperature range, good flame retardant performance and excellent self-healing performance, and is suitable for the automotive industry, electronic equipment, and healthcare equipment.
Smart Images

Figure CN117986891B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of multifunctional materials, and in particular to an ultra-tough, high-strength, flame-retardant, self-healing elastomer composite material and a preparation method thereof. Background Art
[0002] Elastomer materials are widely used in the automotive industry, electronics, healthcare, wearable devices and other fields due to their unique viscoelasticity and excellent comprehensive properties. However, there are inherent conflicts between the properties of elastomers. The first is the conflict between toughness and strength. Practical applications usually require elastomeric materials to have high strength and high toughness. The high strength of elastomers usually requires that the polymer network has a certain rigidity, regularity or high cross-linking density in the structure, so as to limit the movement and slippage of the polymer chain, and not dissipate too much energy during loading and unloading; while the toughness of elastomers usually requires that the material has a large amount of energy dissipation during loading and unloading, so as to achieve the purpose of inhibiting crack propagation. It can be seen that these two properties are often in conflict with each other in the same material, which is the main reason why few elastomeric materials can have both high strength and high toughness. The second is the conflict between strength and self-healing properties. Since the self-healing properties of materials can intuitively extend the service life of materials, they have attracted much attention in recent years. Generally, the self-healing of materials is achieved by the diffusion of molecular chains at the damaged interface of the material or the recombination of weak interaction forces at the interface. The former requires the molecular chain to have good mobility, and the latter requires the material to have a weak cross-linking structure. No matter which structure is used, it conflicts with the high-strength material structure, so few materials have both high self-healing properties and high strength. Therefore, how to prepare elastomers with excellent self-healing properties, high strength and high toughness has always been the research goal of researchers.
[0003] In addition, with the development of science and technology and the progress of the times, people's design and development of new materials are no longer limited to high mechanical properties, and their attention to material functionality is also growing. Among them, the most prominent functional demand is the demand for damping performance that can solve the vibration, impact and noise generated in the fields of transportation, machinery, construction, architecture, furniture and electrical appliances. The damping performance of elastomers is mainly dominated by the viscoelastic transition zone between its glassy state and rubbery state, which is close to or above the glass transition temperature. The changes in chain conformation in this temperature range cannot follow the applied mechanical or acoustic vibration, resulting in effective internal friction and energy dissipation. Conventional elastomers are limited in their application due to their low glass transition temperature and narrow damping temperature range. This is because in the process of engineering application, materials usually need to have good damping performance at or above room temperature and a wide damping temperature range (>60℃) to achieve a good damping effect.
[0004] In summary, the key to the preparation and application of high-performance multifunctional elastomeric composites is to prepare a composite material that has high strength, high toughness, high self-healing efficiency and wide temperature range damping performance that meets engineering standards, solve the scientific problems of low glass transition temperature and small damping temperature range of existing elastomeric composites, and then break through the technical bottleneck of the mutual constraints between self-healing performance and mechanical properties of elastomeric composites. Summary of the invention
[0005] In order to solve the above technical problems, the purpose of the present invention is to provide an ultra-tough, high-strength, flame-retardant, self-healing elastomer composite material and a preparation method thereof, so as to solve the problems of the mutual constraints between the self-healing properties and the mechanical properties of the existing elastomer composite materials, as well as the low glass transition temperature and small damping temperature range of the elastomer composite materials.
[0006] The technical solution of the present invention to solve the above key problems is as follows:
[0007] A method for preparing an ultra-tough, high-strength, flame-retardant, self-repairing elastomer composite material comprises the following steps:
[0008] (1) mixing component A with deionized water, ball-milling the mixture, and then freezing the mixture to obtain ice cube I, wherein component A is tannic acid, chitosan, or dopamine;
[0009] (2) adding the ice cube I obtained in step (1) to a sodium dihydrogen phosphate solution or a potassium dihydrogen phosphate solution, stirring until the ice cube is completely melted, and performing a second freezing treatment to obtain ice cube II;
[0010] (3) Blending the calcium chloride solution, the aqueous polyurethane solution and the ice cube II obtained in step (2), stirring until the ice cube is completely melted, vacuum filtering and drying to obtain the product.
[0011] The beneficial effects of the present invention are as follows: the present invention performs coordination and cross-linking at the solid-liquid interface of water, and performs coordination and cross-linking treatment on ice block I through sodium dihydrogen phosphate solution, thereby achieving deprotonation of component A and generating phosphoric acid at the same time, and phosphoric acid can perform intermolecular hydrogen bonding with unprotonated hydroxyl groups in component A at the solid-liquid interface of water, thereby effectively improving the density of dynamic hydrogen bonds in the system; at the same time, aqueous polyurethane solution and calcium chloride solution are used to form ion coordination on component A in ice block II at the solid-liquid interface of water, thereby further improving the types and density of dynamic bonds in the system; through the above two coordination and cross-linking treatments, a large number of dynamic coordination bonds and hydrogen bonding effects are introduced into the aqueous polyurethane matrix, thereby effectively improving the mechanical properties, self-healing properties, damping properties and flame retardant properties of the prepared composite material.
[0012] Furthermore, in step (1), the mass volume ratio of component A to deionized water is 3-7 g:80-120 mL.
[0013] Preferably, in step (1), the mass volume ratio of component A to deionized water is 4 g:100 mL.
[0014] Furthermore, the ball milling conditions in step (1) are: intermittent ball milling, rotating for 100-150 minutes and stopping for 8-12 minutes, the ball milling time is 24-36 hours, and the rotation speed is 400-500 rpm.
[0015] Preferably, the ball milling conditions in step (1) are: intermittent ball milling, rotating for 120 minutes and stopping for 10 minutes, the ball milling time is 30 hours, and the rotation speed is 450 rpm.
[0016] The beneficial effect of adopting the above further technical solution is that part of the phenolic hydroxyl groups in tannic acid can be oxidized by intermittent ball milling to prevent the formation of intramolecular hydrogen bonds in the polymer matrix.
[0017] Furthermore, the freezing treatment in step (1) is carried out at a temperature of -50 to -30°C and for a time of 6 to 12 hours.
[0018] Preferably, the freezing treatment in step (1) is carried out at a temperature of -40°C and for a period of 9 hours.
[0019] Furthermore, in step (2), the concentration of the sodium dihydrogen phosphate solution or potassium dihydrogen phosphate solution is 28-40 mg / mL; and the volume ratio of ice cube I to the sodium dihydrogen phosphate solution is 360-440 mL:80-120 mL.
[0020] Preferably, the concentration of the sodium dihydrogen phosphate solution or potassium dihydrogen phosphate solution in step (2) is 36 mg / mL; and the volume ratio of ice cube I to the sodium dihydrogen phosphate solution is 400 mL:100 mL.
[0021] Furthermore, in step (2), the stirring speed is 400-700 rpm; the freezing treatment temperature is -50 to -30°C, and the time is 6-12 hours.
[0022] Preferably, the stirring speed in step (2) is 450 rpm; the freezing treatment temperature is -40°C and the time is 9 hours.
[0023] The beneficial effect of adopting the above further technical scheme is as follows: the present invention continuously stirs the ice cube I in the sodium dihydrogen phosphate solution until it is completely dissolved to carry out coordination and cross-linking reactions. During the dissolution of the ice cube, component A and disodium hydrogen phosphate are coordinated and cross-linked step by step, which, on the one hand, avoids agglomeration caused by a large amount of hydroxyl groups contained in the component A solution being directly added. On the other hand, component A can be gradually deprotonated by the sodium dihydrogen phosphate solution to generate phosphoric acid, and then intermolecular hydrogen bonding forces are formed with the non-deprotonated hydroxyl groups in component A at the interface between phosphoric acid and the solid-liquid two phases, thereby increasing the density of dynamic hydrogen bonds in the system.
[0024] Furthermore, in step (3), the concentration of the calcium chloride solution is 6-9 mg / mL; the solid content of the aqueous polyurethane solution is 50-70%; and the mass volume ratio of ice cube II, aqueous polyurethane solution and calcium chloride solution is 35-75 mL: 1-3 g: 35-75 mL.
[0025] Preferably, the concentration of the calcium chloride solution in step (3) is 7.2 mg / mL; the solid content of the aqueous polyurethane solution is 60%; and the mass volume ratio of ice cube II, aqueous polyurethane solution and calcium chloride solution is 55 mL:3 g:55 mL.
[0026] Furthermore, in step (3), the stirring speed is 500-700 rpm; the filtration is performed using a polypropylene filter membrane with a pore size of 0.1-1 μm; the drying temperature is 20-30° C., and the drying time is 8-24 h.
[0027] Preferably, the stirring speed in step (3) is 600 rpm; the filtration is performed using a polypropylene filter membrane with a pore size of 0.22 μm; the drying temperature is 25° C. and the drying time is 16 h.
[0028] The beneficial effects of adopting the above further technical scheme are as follows: the present invention coordinates and hydrogen-bonds ice cube II in a mixed solution of calcium chloride and aqueous polyurethane, and gradually dissolves the ice cube during stirring to carry out step-by-step coordination and cross-linking. On the one hand, it effectively avoids agglomeration caused by a large amount of hydroxyl groups contained in the solution of component A, and on the other hand, the calcium ions in the solution form ionic coordination with component A in the solid-liquid state of water, further increasing the types and density of dynamic bonds in the system.
[0029] An ultra-tough, high-strength, flame-retardant, self-repairing elastomer composite material is prepared by the above-mentioned preparation method.
[0030] The beneficial effects of the present invention are as follows: the ultra-tough, high-strength, flame-retardant and self-healing elastomer composite material prepared by the present invention has high toughness, high strength, high elongation at break, high modulus, a wide damping temperature range, good flame retardant properties and excellent self-healing properties.
[0031] The above-mentioned ultra-tough, high-strength, flame-retardant, self-healing elastomer composite material is used in the automotive industry, electronic equipment or medical care equipment.
[0032] The present invention has the following beneficial effects:
[0033] (1) The present invention prepares a self-healing elastomer composite material with super toughness, high strength, high modulus, wide temperature range damping and flame retardancy by introducing high-density dynamic hydrogen bonds and coordination bonds into a waterborne polyurethane matrix. By adopting a freezing treatment and a gradual dissolution reaction of ice cubes in the reaction solution, on the one hand, it effectively avoids the direct addition of component A solution containing a large amount of hydroxyl groups causing agglomeration, and on the other hand, a large amount of high-density dynamic hydrogen bonds and multiple coordination bonds are added to the system, providing a new design concept and idea for the preparation of high-performance polymer composite materials.
[0034] (2) The ultra-tough, high-strength, flame-retardant, self-healing elastomer composite material prepared by the present invention has high toughness (1156MJ / m 3 ), high strength (52.4MPa), high elongation at break (5307%), high modulus (295MPa), wide damping temperature range (greater than 80°C), good flame retardant properties and excellent self-healing properties.
[0035] (3) The method of the present invention has the advantages of simple process, strong controllability, good stability, mild reaction conditions, and low cost, and the overall process is conducive to large-scale industrial processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The mechanical properties test results of the ultra-tough, high-strength, flame-retardant, self-healing elastomer composite material in Test Example 1, wherein (a) is a stress-strain curve graph, and (b) is a stress, strain, and toughness bar graph;
[0037] Figure 2 The storage modulus test result of the ultra-tough, high-strength, flame-retardant, self-healing elastomer composite material in Test Example 2;
[0038] Figure 3 is a curve diagram showing the change in loss factor of the ultra-tough, high-strength, flame-retardant, self-healing elastomer composite material with temperature in Test Example 3;
[0039] Figure 4 These are the flame retardant performance test results of the ultra-tough, high-strength, flame retardant, self-healing elastomer composite material in Test Example 4. DETAILED DESCRIPTION
[0040] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0041] Embodiment 1:
[0042] A method for preparing an ultra-tough, high-strength, flame-retardant, self-repairing elastomer composite material comprises the following steps:
[0043] (1) Weigh 4 g of tannic acid and put it into a ball mill filled with 100 mL of deionized water. The ball mill was symmetrically placed in a ball mill for ball milling. The ball milling program was set as follows: the rotation speed was 450 rpm, the ball milling was performed for 30 h, and the ball milling was performed intermittently, with a 10-min stop after every 120 min of rotation.
[0044] (2) removing the solution after ball milling in step (1) and freezing it at a temperature of -40°C for 9 hours to obtain ice block I.
[0045] (3) adding ice cube I obtained in step (2) into 100 mL of 36 mg / mL sodium dihydrogen phosphate solution, stirring at 400 rpm until the ice cube is completely melted, and then freezing the mixed solution again at a freezing temperature of -40°C for 9 hours to obtain ice cube II.
[0046] (4) 55 mL of ice cube II obtained in step (3), 3 g of an aqueous polyurethane solution with a solid content of 60%, and 55 mL of a calcium chloride solution with a concentration of 7.2 mg / mL were mixed, and stirred at a speed of 400 rpm until the ice cube was completely melted, and then filtered through a polypropylene filter membrane with a pore size of 0.22 μm, and finally dried at 25°C for 16 hours to obtain an ultra-tough, high-strength, flame-retardant, self-healing elastomer composite material.
[0047] Embodiment 2:
[0048] A method for preparing an ultra-tough, high-strength, flame-retardant, self-repairing elastomer composite material comprises the following steps:
[0049] (1) Weigh 4 g of chitosan and put it into a ball mill filled with 100 mL of deionized water. The ball mill was symmetrically placed in a ball mill for ball milling. The ball milling program was set as follows: the rotation speed was 450 rpm, the ball milling was performed for 30 h, and the ball milling was performed intermittently, with a 10-min stop after every 120 min of rotation.
[0050] (2) removing the solution after ball milling in step (1) and freezing it at a temperature of -40°C for 9 hours to obtain ice block I.
[0051] (3) adding ice cube I obtained in step (2) into 100 mL of 36 mg / mL sodium dihydrogen phosphate solution, stirring at 400 rpm until the ice cube is completely melted, and then freezing the mixed solution again at a freezing temperature of -40°C for 9 hours to obtain ice cube II.
[0052] (4) 55 mL of ice cube II obtained in step (3), 3 g of an aqueous polyurethane solution with a solid content of 60%, and 55 mL of a calcium chloride solution with a concentration of 7.2 mg / mL were mixed, and stirred at a speed of 400 rpm until the ice cube was completely melted, and then filtered through a polypropylene filter membrane with a pore size of 0.22 μm, and finally dried at 25°C for 16 hours to obtain an ultra-tough, high-strength, flame-retardant, self-healing elastomer composite material.
[0053] Embodiment 3:
[0054] A method for preparing an ultra-tough, high-strength, flame-retardant, self-repairing elastomer composite material comprises the following steps:
[0055] (1) Weigh 4 g of dopamine and put it into a ball mill filled with 100 mL of deionized water. The ball mill was symmetrically placed in a ball mill for ball milling. The ball milling program was set as follows: the rotation speed was 450 rpm, the ball milling was performed for 30 h, and the ball milling was performed intermittently, with a 10-min stop after every 120 min of rotation.
[0056] (2) removing the solution after ball milling in step (1) and freezing it at a temperature of -40°C for 9 hours to obtain ice block I.
[0057] (3) adding ice cube I obtained in step (2) into 100 mL of 36 mg / mL sodium dihydrogen phosphate solution, stirring at 400 rpm until the ice cube is completely melted, and then freezing the mixed solution again at a freezing temperature of -40°C for 9 hours to obtain ice cube II.
[0058] (4) 55 mL of ice cube II obtained in step (3), 3 g of an aqueous polyurethane solution with a solid content of 60%, and 55 mL of a calcium chloride solution with a concentration of 7.2 mg / mL were mixed, and stirred at a speed of 400 rpm until the ice cube was completely melted, and then filtered through a polypropylene filter membrane with a pore size of 0.22 μm, and finally dried at 25°C for 16 hours to obtain an ultra-tough, high-strength, flame-retardant, self-healing elastomer composite material.
[0059] Embodiment 4:
[0060] A method for preparing an ultra-tough, high-strength, flame-retardant, self-repairing elastomer composite material comprises the following steps:
[0061] (1) Weigh 4 g of tannic acid and put it into a ball mill filled with 100 mL of deionized water. The ball mill was symmetrically placed in a ball mill for ball milling. The ball milling program was set as follows: the rotation speed was 450 rpm, the ball milling was performed for 30 h, and the ball milling was performed intermittently, with a 10-min stop after every 120 min of rotation.
[0062] (2) removing the solution after ball milling in step (1) and freezing it at a temperature of -40°C for 9 hours to obtain ice block I.
[0063] (3) adding the ice cube I obtained in step (2) into 100 mL of a 36 mg / mL potassium dihydrogen phosphate solution, stirring at 400 rpm until the ice cube is completely melted, and then freezing the mixed solution again at a freezing temperature of -40°C for 9 hours to obtain ice cube II.
[0064] (4) 55 mL of ice cube II obtained in step (3), 3 g of an aqueous polyurethane solution with a solid content of 60%, and 55 mL of a calcium chloride solution with a concentration of 10 mg / mL were mixed, and stirred at a speed of 400 rpm until the ice cube was completely melted, and then filtered through a polypropylene filter membrane with a pore size of 0.22 μm, and finally dried at 25°C for 16 hours to obtain an ultra-tough, high-strength, flame-retardant, self-healing elastomer composite material.
[0065] Embodiment 5:
[0066] A method for preparing an ultra-tough, high-strength, flame-retardant, self-repairing elastomer composite material comprises the following steps:
[0067] (1) Weigh 4 g of chitosan and put it into a ball mill filled with 100 mL of deionized water. The ball mill was symmetrically placed in a ball mill for ball milling. The ball milling program was set as follows: the rotation speed was 450 rpm, the ball milling was performed for 30 h, and the ball milling was performed intermittently, with a 10-min stop after every 120 min of rotation.
[0068] (2) removing the solution after ball milling in step (1) and freezing it at a temperature of -40°C for 9 hours to obtain ice block I.
[0069] (3) adding the ice cube I obtained in step (2) into 100 mL of a 36 mg / mL potassium dihydrogen phosphate solution, stirring at 400 rpm until the ice cube is completely melted, and then freezing the mixed solution again at a freezing temperature of -40°C for 9 hours to obtain ice cube II.
[0070] (4) 55 mL of ice cube II obtained in step (3), 3 g of an aqueous polyurethane solution with a solid content of 60%, and 55 mL of a calcium chloride solution with a concentration of 7.2 mg / mL were mixed, and stirred at a speed of 600 rpm until the ice cube was completely melted, and then filtered through a polypropylene filter membrane with a pore size of 0.22 μm, and finally dried at 25°C for 16 h to obtain an ultra-tough, high-strength, flame-retardant, self-healing elastomer composite material.
[0071] Embodiment 6:
[0072] A method for preparing an ultra-tough, high-strength, flame-retardant, self-repairing elastomer composite material comprises the following steps:
[0073] (1) Weigh 4 g of tannic acid and put it into a ball mill filled with 100 mL of deionized water. The ball mill was symmetrically placed in a ball mill for ball milling. The ball milling program was set as follows: the rotation speed was 450 rpm, the ball milling was performed for 30 h, and the ball milling was performed intermittently, with a 10-min stop after every 120 min of rotation.
[0074] (2) removing the solution after ball milling in step (1) and freezing it at a temperature of -40°C for 9 hours to obtain ice block I.
[0075] (3) adding ice cube I obtained in step (2) into 100 mL of 36 mg / mL sodium dihydrogen phosphate solution, stirring at 400 rpm until the ice cube is completely melted, and then freezing the mixed solution again at a freezing temperature of -40°C for 9 hours to obtain ice cube II.
[0076] (4) 55 mL of ice cube II obtained in step (3), 3 g of an aqueous polyurethane solution with a solid content of 60%, and 55 mL of a calcium chloride solution with a concentration of 7.2 mg / mL were mixed, and stirred at a speed of 600 rpm until the ice cube was completely melted, and then filtered through a polypropylene filter membrane with a pore size of 0.22 μm, and finally dried at 25°C for 16 h to obtain an ultra-tough, high-strength, flame-retardant, self-healing elastomer composite material.
[0077] Comparative Example 1:
[0078] A method for preparing a composite material having self-healing properties and damping properties comprises the following steps:
[0079] (1) 3.5 g of polyurea-urethane (synthesis method refers to Fang L, Chen T, Li X, et al. Wide-temperature range damping polyurea-urethane blends with self-healing capability [J]. Construction and Building Materials, 2020, 262(3): 119991.) and 2.5 g of vinyl resin were dissolved in 100 mL of DMF solution, and then 1 g of vulcanizer BMI was added to the solution and stirred until it was completely dissolved.
[0080] (2) pouring the mixed solution obtained in step (1) into a mold and drying it at 60° C. for 24 hours to obtain a composite material with self-healing and damping properties.
[0081] Test Example 1: Mechanical Properties
[0082] The ultra-tough, high-strength, flame-retardant, self-healing elastomer composite material of Example 1 was taken as a sample for experiment, and the mixing volume of the calcium chloride solution in step (4) in Example 1 was changed to 35 mL, 45 mL, 65 mL and 75 mL for sample preparation, and the samples were named 35, 45, 55, 65 and 75 according to the mixing volume of their calcium chloride solutions, respectively. The mechanical properties of the samples were tested by a tensile testing machine, and the composite material prepared in Comparative Example 1 was used as a control.
[0083] The experimental results are as follows Figure 1 shown.
[0084] According to the results in the figure, the samples prepared from Examples 1 and 4-7 of the present invention all exhibited high stress, strain and toughness, with the highest toughness reaching 1156 MJ·m 3 , tensile strength can reach 52.4MPa, and elongation at break can reach 5307%, which has extremely high mechanical properties. The tensile strength of the composite material prepared in Comparative Example 1 is only 14.3MPa, and the elongation at break is 237%, which are significantly lower than the composite material prepared in the embodiment of the present invention. The results show that the method of the present invention can significantly improve the mechanical properties of the composite material.
[0085] Test Example 2: Storage modulus
[0086] The ultra-tough, high-strength, flame-retardant, self-healing elastomer composite materials prepared in Example 1 and Examples 4-7 were taken as samples for experimentation, and the mixed volumes of their calcium chloride solutions were named 35, 45, 55, 65 and 75, respectively. The storage modulus of the composite materials at room temperature was tested by a dynamic mechanical analyzer.
[0087] The experimental results are as follows Figure 2 shown.
[0088] according to Figure 2 It can be seen from the experimental results that the composite materials prepared in Example 1 and Examples 4-7 of the present invention have a higher storage modulus at room temperature, and the storage modulus gradually increases with the increase of the mixing volume of the calcium chloride solution. When the mixing volume of the calcium chloride solution is 75 mL, the storage modulus of the prepared composite material at room temperature is as high as 295 MPa, which has the characteristics of high storage modulus.
[0089] Test Example 3: Damping Performance
[0090] The ultra-tough, high-strength, flame-retardant, self-healing elastomer composites prepared in Example 1 and Examples 4-7 were taken as samples for experimentation, and the mixed volumes of their calcium chloride solutions were named 35, 45, 55, 65 and 75, respectively. The loss factor tanδ of the composites was tested with a dynamic mechanical analyzer to show a curve varying with temperature to test the damping performance of the composites. When tanδ>0.3, the composite material indicated that the composite material had damping performance. The composite material prepared in Comparative Example 1 was used as a control.
[0091] The experimental results are as follows Figure 3 shown.
[0092] according to Figure 3 It can be seen from the experimental results that the composite materials prepared in Example 1 and Examples 4-7 of the present invention exhibit relatively excellent damping performance, and the temperature range of the damping performance is greater than 80°C, and the maximum value of tanδ is also greater than 0.5, showing strong damping performance. However, the composite material prepared in Comparative Example 1 was tested to have a maximum value of tanδ less than 0.5, and the temperature range of the damping performance is about 40°C, which is a large gap from the composite material prepared in the embodiment of the present invention. The results show that the method of the present invention can achieve a significant improvement in the damping performance of the composite material, and can achieve a damping effect at a variety of temperatures.
[0093] Test Example 4: Flame retardant properties
[0094] The flame retardant properties of the ultra-tough, high-strength, flame-retardant self-healing elastomer composite material prepared in Example 1 and the composite material prepared in Comparative Example 1 were tested.
[0095] The test method is: ignite the sample and take a photo with a digital camera to observe the burning condition of the sample.
[0096] The experimental results are as follows Figure 4 As shown, according to Figure 4The results show that the composite material prepared in Example 1 of the present invention was ignited twice, and the flames of the composite material were completely extinguished within 5 seconds after ignition, indicating that the ultra-tough, high-strength, flame-retardant, self-healing elastomer composite material prepared in the present invention has a strong flame retardant ability. However, the composite material prepared in Comparative Example 1 was quickly burned out after the first ignition in the flame retardant performance test experiment, and did not have flame retardant ability.
[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an ultra-tough, high-strength, flame-retardant, self-repairing elastomer composite material, characterized in that: The following steps are involved: (1) mixing component A with deionized water, ball-milling the mixture, and then freezing the mixture to obtain ice cube I, wherein component A is tannic acid, chitosan, or dopamine; (2) adding ice cube I obtained in step (1) to a sodium dihydrogen phosphate solution or a potassium dihydrogen phosphate solution, stirring until the ice cube is completely melted, and then performing a second freezing treatment to obtain ice cube II; (3) blending the calcium chloride solution, the aqueous polyurethane solution and the ice cube II obtained in step (2), stirring until the ice cube is completely melted, vacuum filtering and drying to obtain the product; In step (1), the mass volume ratio of component A to deionized water is 3-7 g: 80-120 mL; The concentration of the sodium dihydrogen phosphate solution or potassium dihydrogen phosphate solution in step (2) is 28-40 mg / mL; the volume ratio of ice cube I to the sodium dihydrogen phosphate solution or potassium dihydrogen phosphate solution is 360-440 mL:80-120 mL; The concentration of the calcium chloride solution in step (3) is 6-9 mg / mL; the solid content of the aqueous polyurethane solution is 50-70%; and the mass volume ratio of ice cube II, aqueous polyurethane solution and calcium chloride solution is 35-75 mL: 1-3 g: 35-75 mL.
2. The method for preparing the ultra-tough, high-strength, flame-retardant, self-healing elastomer composite material according to claim 1, characterized in that: The ball milling conditions in step (1) are: intermittent ball milling, rotating for 100-150 minutes and stopping for 8-12 minutes, the ball milling time is 24-36 hours, and the rotation speed is 400-500 rpm.
3. The method for preparing the ultra-tough, high-strength, flame-retardant, self-repairing elastomer composite material according to claim 1, characterized in that: The freezing treatment in step (1) is carried out at a temperature of -50 to -30 °C and for a period of 6 to 12 h.
4. The method for preparing the ultra-tough, high-strength, flame-retardant, self-repairing elastomer composite material according to claim 1, characterized in that: The stirring speed in step (2) is 500-700 rpm; the freezing treatment temperature is -50~-30°C and the time is 6-12h.
5. The method for preparing the ultra-tough, high-strength, flame-retardant, self-repairing elastomer composite material according to claim 1, characterized in that: In the step (3), the stirring speed is 400-700 rpm; the filtration is performed using a polypropylene filter membrane with a pore size of 0.1-1 μm; the drying temperature is 20-30°C and the drying time is 8-24 h.
6. An ultra-tough, high-strength, flame-retardant, self-repairing elastomer composite material, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 5.
7. Application of the ultra-tough, high-strength, flame-retardant, self-healing elastomer composite material according to claim 6 in the automotive industry, electronic equipment or medical care equipment.
Citation Information
Patent Citations
Preparation method of low specific gravity self-repaired PVC cable material
CN109181141A
Flame-retardant aerogel with self-repairing performance and preparation method thereof
CN110204796A